KONDISI KOMUNITAS TERUMBU KARANG DI PANTAI BIAS PUTIH DESA BUGBUG KECAMATAN KARANGASEM KABUPATEN KARANGASEM BALI - Restu, I Wayan (Bumi Lestari; Vol 11 No 1 (2011), 2011)
The extent of coral reefs in Bali province is 7200 ha. It spreads out in almost all districts, except Bangli. The condition status of coral reefs has been greatly reduced recently due to rampant fish bombing activities, making sea rocks, seaweed cultivation and the rapid growth of tourism. The conditions status of coral reefs in Bali (2010) are as follows: excellent (3.8%), good (35.8%), moderate (39.6%) and bad (20.8%). Research on the condition status of coral reefs in Bias Putih Beach of Bugbug Village, Karangasem District, Karangasem Regency, Bali is intended to provide basic data about the condition status of coral reefs that can be used as a consideration on its management. Manta Tow Survey and Line Intercept Transect were implemented as methods on this research. The results showed the condition status of coral reefs was between moderate to good with the description as follows: manta tow results showed that living coral cover were categorized between 2 and 3, with the percentage of cover between 11-50 %, while soft corals were categorized between 1 and 3, and the results of Line Intercept transect were categorized into showing up very well with the percentage of living coral coverage ranged between 66.34% and 87.36%. Species diversity of coral was observed to be high with H values ranging between 3,133934 and 3,167543 and its equitability values was observed to be high ranged between 0,94340 and 0,9535. Thus, it is concluded that the condition status of coral reefs in Bias Putih Beach, of Bugbug Village, Karangasem, Bali to be categorized into good or very good.
Keywords: community, corals reef, status, diversity, equitability